Studi Rekonfigurasi Jaringan Distribusi 20 kV pada Penyulang DPRD ULP Cianjur Kota Menggunakan ETAP - Giri Angga Setia; Fathul Muhammad Nur; Fauzia Haz (EPSILON: Journal of Electrical Engineering and Information Technology, 2023)
In the distribution of electricity from electric power sources to consumers who are located far apart, they always experience losses, namely in the form of voltage drops and power losses. However, the voltage loss that occurs in the process of distributing electrical energy is a waste of energy if it is not controlled optimally. Concerning the quality of service, the main factor which becomes the benchmark is the continuity of service and the quality of service voltage. The impact of these losses results in low levels of service quality to customers. Analysis of voltage drop and power loss is needed to determine the size of the voltage drop at the end of the DPRD feeder network. The calculation of voltage drops and power loss uses simulation results of ETAP method. The results of mathematical calculations and simulations are analyzed to determine the factors that cause the voltage quality at the end of the DPRD feeder network to be below the standard service voltage of 20 kV. The results of the analysis and simulation show that the factors that cause the voltage quality at the end of the DPRD feeder to be below the standard of service quality level are the transformer loading system, the type of conductor, and the distance of the substation to the far end of the feeder network. Then the problem was resolved by changing the type of conductor and reconfiguring it by shifting part of the load to the Lampegan feeder so that the voltage profile at the end of the DPRD Feeder was initially 17.527 kV after reconfiguration increased to 18.137 kV.